Efektivitas Metode Tadabur Alam dalam Meningkatkan Prestasi Belajar Pendidikan Agama Islam di SD Inpres 15 Wamega, Kab. Raja Ampat - Pongoh, Arianti; Amin, Surahman; Maskur, Maskur; Waris, Ahmad Mustamir; Jafar N, Muhammad Kamil (LPPM IAIN Sorong, 2025)
This study aims to analyze: (1) the implementation of the nature contemplation method at SD Inpres 15 Wamega, Raja Ampat Regency, (2) the effectiveness of the nature contemplation method in improving learning achievement in Islamic Religious Education, and (3) supporting and inhibiting factors in the implementation of the nature contemplation method. This study uses a qualitative approach with a phenomenological research type. Data collection was carried out through observation, interviews, and documentation, with data analysis using descriptive techniques and data validity through source triangulation. The results of the study indicate that: (1) The implementation of the nature contemplation method was carried out by inviting students to observe the surrounding nature to analyze learning materials in a pleasant atmosphere. (2) The nature contemplation method is effective in improving student learning achievement in Islamic Religious Education subjects, as indicated by an increase in student understanding and evaluation scores. (3) Supporting factors include Wamega's strategic natural conditions, teacher support, and parental cooperation, while inhibiting factors include teacher professionalism, teacher educational qualifications, and unpredictable weather conditions. The implication of this study is the need for school policies in developing a local curriculum based on nature contemplation to improve student learning achievement.